2019
DOI: 10.3390/plants8100408
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analyses of the Distribution and Function of Diazotrophic Rhizobia and Methanotrophs in the Tissues and Rhizosphere of Non-Leguminous Plants

Abstract: Biological nitrogen fixation (BNF) by plants and its bacterial associations represent an important natural system for capturing atmospheric dinitrogen (N2) and processing it into a reactive form of nitrogen through enzymatic reduction. The study of BNF in non-leguminous plants has been difficult compared to nodule-localized BNF in leguminous plants because of the diverse sites of N2 fixation in non-leguminous plants. Identification of the involved N2-fixing bacteria has also been difficult because the major ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 118 publications
0
14
0
1
Order By: Relevance
“…R2-708 (OTU321) under aCO 2 treatment (Figure 5C). Rhizobium is a well-known N 2 -fixing bacterium that is frequently detected in legumes as well as in rice roots (Zahran, 1999;Bao et al, 2014a;Yoneyama et al, 2019) and other plants. Heterotrophic N 2 -fixing bacteria, including Rhizobium, are often inhibited by nitrogen inputs (Kumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R2-708 (OTU321) under aCO 2 treatment (Figure 5C). Rhizobium is a well-known N 2 -fixing bacterium that is frequently detected in legumes as well as in rice roots (Zahran, 1999;Bao et al, 2014a;Yoneyama et al, 2019) and other plants. Heterotrophic N 2 -fixing bacteria, including Rhizobium, are often inhibited by nitrogen inputs (Kumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…N fertilization decreased the relative abundance of root-associated bacteria community, especially type II methanotrophs and Bradyrhizobium (Ikeda et al, 2014). Generally, N fertilizer inputs inhibit N 2 fixation and influence the N 2 -fixing bacterial community (Kumar et al, 2018), which can convert atmospheric N 2 gas to ammonium and make it available to plants as a major nutrient (Yoneyama et al, 2019). eCO 2 can increase the N demand for plants, which is beneficial for N 2 fixation (Luo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates produced by photosynthesis are stored in the stem mainly as starch and sucrose in rice (Yoshida, 1972 ) as shown in this study ( Table 2 , Figure 2 ). In the mature stem of sugarcane, about 10–20% of the accumulated sugars were present in the apoplast and contributed to high endophytic BNF (Welbaum and Meinzer, 1990 ; Dong et al, 1994 ; Yoneyama et al, 2019 ). The shading experiment also indicated that changes in sugar are more crucial than starch for the fluctuation of N-fixing activity, since ARA in agpl1 decreased significantly by shading treatment in association with a large decrease in sugar as compared with Nipponbare ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the studies conducted, active expression of NifH, one of the proteins that compose the nitrogenase enzyme, is phylogenetically similar to that of the Bradyrhizobium sp., and Azorhizobium sp. was observed in the N-fixing sugarcane stems, sweet potato stems, and tuberous roots (Terakado-Tonooka et al, 2008 ; Fischer et al, 2012 ; Yoneyama et al, 2019 ). In rice roots as well, active BNF by methane-oxidizing methanotrophs on consuming CH 4 as a carbon source has also been reported (Bao et al, 2014 ; Shinoda et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A produção da soja representa 50% da área total cultivada com leguminosas, e é responsável por fixar 16,4 Tg N anualmente, o que equivale a quase 80% de todo nitrogênio fixado pelas leguminosas (HERRIDGE et al, 2008). Apesar de associações simbióticas com rizóbios não serem naturais com plantas não-leguminosas, trabalhos mostram que culturas como arroz, milho, cana-de-açúcar, e gramíneas são capazes de fixar N2 por meio de relações menos especializadas com microrganismos de vida livre ou associados às plantas (HERRIDGE et al, 2008;YONEYAMA et al, 2019).…”
Section: Influências Antropogênicas No Ciclo Do Nitrogêniounclassified